Strategy, Training, and Career as Empowerment Factors for Young People: Strategi, Pelatihan, dan Karir sebagai Faktor Pemberdayaan Generasi Muda - Lubis, Miftahul Jannah; Rizky, M. Chaerul; Siregar, Reni Astrya; Priatna, Sabillah; Tiara, Tiara (Indonesian Journal of Innovation Studies, 2025)
General Background: Rural development hinges on the active participation and empowerment of youth as agents of change. Specific Background: In Desa Belawan Bahagia, Kecamatan Medan Belawan, with a population of 13,630, young people face limited access to training and career development opportunities, hindering their contribution to local progress. Knowledge Gap: Despite existing rural empowerment programs, empirical studies on the integrated influence of strategic village planning, training, and career development on youth empowerment remain limited. Aim: This study aims to analyze the influence of village strategy (X₁), training (X₂), and career development (X₃) on youth empowerment in Desa Belawan Bahagia. Results: Using a quantitative survey method with 99 randomly selected respondents, and applying multiple linear regression analysis, the results show that career development has a significant positive effect on youth empowerment (p < 0.001), while village strategy and training do not show statistically significant effects. Novelty: This study highlights career development as a dominant driver of rural youth empowerment, a factor often underemphasized in rural development discourse. Implications: The findings suggest the need for targeted investment in structured career development programs to optimize the role of youth in village transformation.Highlights: Career development is the most influential factor in empowering rural youth. Village strategy and training showed no significant statistical effect. Focused career programs can accelerate sustainable village transformation. Keywords: Village Strategy, Training, Career Development, Youth Empowerment, Rural Development